Cumulative live birth rates and birth outcomes after IVF/ICSI treatment cycles in young POSEIDON patients: A real-world study - Yan, Enqi; Li, Wenxuan; Jin, Huizi; Zhao, Mengya; Chen, Dan; Hu, Xinyao; Chu, Yifan; Guo, Yaxin; Jin, Lei (Frontiers in Endocrinology, 2023)
Objective: The aim of this study is to describe the cumulative live birth rates (CLBRs) of young women with or without low prognosis according to the POSEIDON criteria after IVF/ICSI cycles and to investigate whether diagnosis of low prognosis increase the risk of abnormal birth outcomes. Design: Retrospective study. Setting: A single reproductive medicine center. Population: From January 2016 to October 2020, there were 17,893 patients (<35 years) involved. After screening, 4,105 women were included in POSEIDON group 1, 1,375 women were included in POSEIDON group 3, and 11,876 women were defined as non-POSEIDON. Intervention(s): Baseline serum AMH level was measured on the D2-D3 of menstrual cycle before IVF/ICSI treatment. Main Outcome Measure(s): cumulative live birth rate (CLBR), birth outcomes Result(s): After 4 stimulation cycles, the CLBRs in POSEIDON groups 1, POSEIDON group 3 and non-POSEIDON group reached 67.9% (95%CI 66.5%-69.3%), 51.9% (95%CI 49.2%-54.5%) and 79.6% (95%CI 78.9%-80.3%), respectively. There was no difference in gestational age, preterm delivery, cesarean delivery and low birth weight infants between the three groups, but macrosomia was significantly higher in non-POSEIDON group, after adjusting for maternal age and BMI. Conclusion(s): POSEIDON group shows lower CLBRs than non-POSEIDON group in young women, while the risk of abnormal birth outcomes in POSEIDON group will not increase. Keyword(s): low prognosis, POSEIDON criteria, IVF/ICSI, cumulative live birth rates, birth outcomes